Investigation into the extended capabilities of the new DPS-4D ionosonde - Ssessanga, Nicholas (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2011)
The DPS-4D is the latest version of digital ionosonde developed by the UMLCAR (University of Massachusetts in Lowell Center for Atmospheric Research) in 2008. This new ionosonde has advances in both the hardware and software which allows for the promised advanced capabilities. The aim of this thesis was to present results from an experiment undertaken using the Hermanus DPS-4D (34.4Â°S 19.2Â°E, South Africa), the first of this version to be installed globally, to answer a science question outside of the normally expected capabilities of an ionosonde. The science question posed focused on the ability of the DPS-4D to provide information on day-time Pc3 pulsations evident in the ionosphere. Day-time Pc3 ULF waves propagating down through the ionosphere cause oscillations in the Doppler shift of High Frequency (HF) radio transmissions that are correlated with the magnetic pulsations recorded on the ground. Evidence is presented which shows that no correlation exists between the ground magnetic pulsation data and DPS-4D ionospheric data. The conclusion was reached that although the DPS-4D is more advanced in its eld of technology than its predecessors it may not be used to observe Pc3 pulsations.
Keywords: Ionosondes; Ionosphere; Ionosphere -- Observations -- South Africa -- Hermanus (Cape of Good Hope); Ionosphere -- Research -- South Africa -- Hermanus (Cape of Good Hope)